A Community-Based Cross-Hospital Study on Human Immune Variability and Its Association with Lifestyle and Environmental Factors: A Community-Based Cross-Hospital Study (مجلة التربوي, 2026)
This study investigates human immune variability across three distinct regions in Western Libya: Al-Khoms, Zliten, and Msallata. Utilizing a community-based, cross-hospital approach, the research examines the association between immune biomarkers, lifestyle factors (sleep, stress, physical activity, diet, smoking), and environmental indicators (Air Quality Index, humidity, temperature, population density). Data from 120 participants, proportionally distributed across Al-Khoms Medical Center (40%), Zliten Medical Center (40%), and Msallata Teaching Hospital (20%), were analyzed. Key findings reveal significant differences in immune biomarkers and lifestyle patterns across the hospitals, with Msallata showing lower inflammation and better sleep, while Zliten exhibited higher stress and C-Reactive Protein (CRP) levels. Strong correlations were, identified between immune status and sleep hours, stress levels, and air quality. Furthermore, machine learning models, particularly Random Forest, demonstrated high accuracy in predicting immune status based on non-clinical variables, highlighting the potential for community health dashboards and early-warning systems. This research underscores the profound impact of environmental and lifestyle conditions on immune health and advocates for integrated monitoring and targeted interventions.